MENINGKATKAN AKTIVITAS DAN KETERAMPILAN BERPIKIR KRITIS MENGGUNAKAN MODEL PANTING PADA SISWA KELAS V - Arif Rahman; Aslamiah (Universitas PGRI Palembang, 2022)
Abstract: This study addresses the issues of low activity, critical thinking skills, and learning outcomes in science class. The objective is to describe the analysis of teacher and student activities and to analyze the improvement of critical thinking skills and learning outcomes. The research uses Classroom Action Research (CAR) conducted over four meetings in a fifth-grade class consisting of 18 students, 8 male and 10 female, at SDN Danda Jaya 3. Qualitative data was obtained through observation of teacher and student activities, as well as student critical thinking skills. The results indicate that the teacher's activities in meetings 1 to 4 were well-implemented. Student activities improved from 44% to 94% throughout meetings 1 to 4, almost entirely meeting the criteria for being active. Student critical thinking skills also improved from 39% to 94% over meetings 1 to 4, meeting almost all criteria for being skilled. The level of student learning outcomes increased from 44% to 100%. Based on the findings, the PANTING teaching model can improve student activity and critical thinking skills. Abstrak: Penelitian ini membahas masalah rendahnya aktivitas, kemampuan berpikir kritis, dan hasil belajar di kelas pada muatan IPA. Tujuannya adalah untuk mendeskripsikan analisis aktivitas guru dan siswa serta menganalisis peningkatan kemampuan berpikir kritis dan hasil belajar. Penelitian ini menggunakan Penelitian Tindakan Kelas (PTK) yang dilakukan selama empat pertemuan di kelas V yang terdiri dari 18 siswa, 8 laki-laki dan 10 perempuan, di SDN Danda Jaya 3. Data kualitatif diperoleh melalui observasi aktivitas guru dan siswa, serta kemampuan berpikir kritis siswa. Hasil penelitian menunjukkan bahwa kegiatan guru dalam pertemuan 1 sampai 4 dilaksanakan dengan baik. Aktivitas siswa meningkat dari 44% menjadi 94% selama pertemuan 1 hingga 4, hampir seluruhnya aktif. Keterampilan berpikir kritis siswa juga meningkat dari 39% menjadi 94% selama pertemuan 1 hingga 4, memenuhi hampir seluruhnya terampil. Hasil belajar siswa meningkat dari 44% menjadi 100%. Berdasarkan temuan, model pengajaran PANTING dapat meningkatkan aktivitas siswa dan kemampuan berpikir kritis.